Issues Concerning the Effects of Overstatement and Underassessment of Intangible Assets - Application Particularities - Mangu (Giurea), Gabriela; Tegledi, Monica Adriana; Dindareanu (Iuga), Viorica (Acta Universitatis Danubius. Œconomica, 2022)
The accurate assessment of the intangible assets is a significant challenge for most entities, regardless of the industry sector. However, situations can arise in accounting where intangible assets may be significantly detracted or overstated and we have chosen to present some of the possible effects of this phenomenon. In this sense, there were analyzed practical aspects regarding the financial statements’ distortion through the overstatement and, respectively, the detraction of intangible assets, as these meant to be recognized in the financial statement and might influence the economic entity’s financial indicators